The recovery group - Morgan, Sarah; Carson, Jerome (Groupwork, 2012)
In this paper we describe the contemporary importance of the recovery approach in mental health services. Recovery is one of the main service drivers. Thus far, much of the focus has been on individuals and their unique recovery journeys. Groupwork, may have a key role to play in the continued development of the recovery approach. We present the Recovery Group, an innovative approach to involving service users in recovery. A ‘colour piece’ illustrates a single groupwork session. If clinicians and policy makers are to truly place service users centre stage in the recovery process, more innovative methods of engagement are needed.